Advancing inclusive growth in Nigeria: The role of financial inclusion in poverty, inequality, household expenditure, and unemployment - Musa Abdullahi Sakanko; Joseph David; Aliyu Musari Onimisi (Indonesian Journal of Islamic Economics Research, 2020)
This study employs ARDL bounds testing technique to examine the effect of financial inclusion on inclusive growth in Nigeria, using quarterly data from 2007-2018. The empirical evidence reveals the presence of cointegration between financial inclusion indicators (account ownership, access to bank, ATM and credit, loans to SMEs and internet usage) and inclusive growth (poverty, household expenditure, employment, and per capita income). The results demonstrate that, while increase in account ownership, and access to bank and ATM raise poverty, and access to credit, loans to SMEs and internet usage reduces employment and per capita income in the long-run, it was also discovered that access to credit reduce poverty and increase household consumption, while account ownership and access to bank increases employment and per capita income in the long-run. In the short-run: lag of account ownership, access to ATM and credit, loan to SMEs and internet usage reduces poverty; lag of household expenditure, account ownership, and access to ATM and lag of internet usage increases household expenditure; lags of access to ATM and lags of internet usage (and account ownership and access to bank) increases employment opportunities (and per capita income); and access to ATM and credit reduces employment and per capita income respectively.